Photoacoustic Spectroscopic Analysis of Electron-Trapping Sites in Titanium(IV) Oxide Photocatalyst Powder Treated by Ball Milling - Shinoda, Tatsuki; Yamaguchi, Yuichi; Kudo, Akihiko; Murakami, Naoya (Journal of physical chemistry. C, 2022)
Photoabsorption of trapped electrons in rutile titanium(IV) oxide (TiO2) before and after ball-milling and annealing treatments was investigated in a wide range of light wavelengths from visible to mid-infrared (IR) regions using photoacoustic spectroscopy (PAS). In the presence of an electron donor under an inert gas atmosphere, photoacoustic signals for all of the samples were increased by ultraviolet irradiation, resulting in the appearance of broad absorption due to electron accumulation in TiO2. For ball-milled TiO2 with a large specific surface area (34 m2 g–1), mid-IR absorption attributed to free electrons and shallowly trapped electrons was smaller than that of the pristine sample with a small specific surface area (2.8 m2 g–1), but broad absorption ascribed to deeply trapped electrons dramatically increased in the range of near-IR to visible regions. This near-IR–visible absorption was slightly observed even in the presence of oxygen, and it was divided into two parts: one was characteristic near-IR absorption of rutile TiO2 having a peak at ∼1.0 eV below the bottom of the conduction band, while the other was ball-milling-induced absorption with a peak at ∼1.7 eV. By annealing treatment, absorptions of free electrons/shallowly trapped electrons and deeply trapped electrons increased and decreased, respectively, although not as much as in the pristine sample. At that time, the specific surface area also decreased to 18 m2 g–1. In the evaluation of photocatalytic activity, pristine TiO2 showed the highest activity for hydrogen (H2) evolution from an aqueous solution containing an electron donor, whereas the rates of H2 evolution for the ball-milled and subsequently annealed samples were 0.21 and 0.34 times lower than that for the pristine sample. Thus, we found from the results of PAS measurements that the main factor governing the photocatalytic activity is not specific surface area but the presence of deeper-energy electron-trapping sites formed by pulverization with ball milling.